Small Loans, Big Dreams: Micro-Entrepreneurs’ Loan Terms And Loan Performance Of Microfinance Institutions In The City Of San Fernando, La Union - John Joshua B. Abellera; Lea Mae E. Alvarado; Trisha Lei B. Dela Cruz; Roan Mae N. Ganuelas; Melanie N. Gaudia (INTERNATIONAL CONFERENCE OF ECONOMICS AND BUSINESS, 2025)
Microfinance Institutions (MFIs) have become instrumental in the realization of Sustainable Development Goals, supporting economic growth and the development of microentrepreneurs worldwide. The study was conducted to describe the micro entrepreneurs’ loan terms, portfolio quality of microfinance institutions, and the relationship between the micro-entrepreneurs’ loan terms and portfolio quality of the microfinance institutions in the City of San Fernando, La Union. The study adopted a cross-sectional survey and correlational research design, and the data were gathered from 17-microfinance institutions using a validated questionnaire and were analyzed using frequency counts, percentage, Spearman’s Rho, and Point-Biserial Correlation. Findings revealed that the respondents MFIs offered flexible loan terms to micro entrepreneurs and have a deteriorating portfolio quality with high levels of portfolio at risk ratio and write-off ratio. Further, the findings revealed that the loan amount and penalties under micro-entrepreneurs’ loan terms have a significant relationship with portfolio quality in terms of write-off ratio.